Operation analysis of the tele-critical care service demonstrates value delivery, service adaptation over time, and distress among tele-providers - Laudanski, Krzysztof; Huffenberger, Ann Marie; Scott, Michael J.; Williams, Maria; Wain, Justin; Jablonski, Juliane; Hanson, C. William (Frontiers in Medicine, 2022)
Background: Our study addresses the gap in characterization of engagements by the remote tele-CCM team with the bedside team. Methods: REDCap self-reported activity log collected engagement duration, triggers (emergency button, tele-CCM software platform, autonomous algorithm, asymmetrical communication platform, phone), expediency, nature (proactive rounding, predetermined task, response to medical needs), communication modes, and acceptance. Seven hospitals with 16 ICUs were overseen between 9/2020 and 9/2021 by team consisting of attending (eMD), nurses (eRN), and respiratory therapists (eRT). Results: 39,915 engagements were registered. eMD had a significantly higher percentage of emergent and urgent engagements (31.9%) versus eRN (9.8%) or eRT (98.2%). The average tele-CCM intervention took 16.1±10.39 minutes for eMD, 18.1±16.23 for eRN, and 8.2±4.98 minutes for eRT with significant variation between engagement types, expediency, hospitals and ICUs types. During the observation period, there was a shift in intervention triggers with the increase in autonomous algorithmic ARDS detection concomitant with predominant utilization of asynchronous communication, phone engagements and the tele-CCM module of EPIC at the expense of the share of proactive rounding. eRT communicated more frequently with bedside staff (%MD=37.8%; %RN=36.8, %RT=49.0% (χ2[2, N=20,223] =1,574.56; p<0.00001) but mostly with eRT. In contrast, the eMD communicated with all ICU stakeholders while the eRN mostly communicated chiefly with the RN and house staff at the bedside. The rate of distress reported by tele-CCM staff was 2% among all interactions, with the entity hospital being the dominant factor. Conclusions: Delivery of tele-CCM services has to be tailored to the needs of the specific beneficiary of tele-CCM services.